2008
DOI: 10.1038/emboj.2008.128
|View full text |Cite
|
Sign up to set email alerts
|

Mre11–Rad50–Nbs1-dependent processing of DNA breaks generates oligonucleotides that stimulate ATM activity

Abstract: DNA double-strand breaks (DSBs) can be processed by the Mre11-Rad50-Nbs1 (MRN) complex, which is essential to promote ataxia telangiectasia-mutated (ATM) activation. However, the molecular mechanisms linking MRN activity to ATM are not fully understood. Here, using Xenopus laevis egg extract we show that MRN-dependent processing of DSBs leads to the accumulation of short singlestranded DNA oligonucleotides (ssDNA oligos). The MRN complex isolated from the extract containing DSBs is bound to ssDNA oligos and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 35 publications
4
93
0
Order By: Relevance
“…Recent studies have indicated that the MRN complex bound to DNA ends may directly activate ATM and/or initiate the nucleation of ATM at DSBs, which leads to its activation (Lee and Paull, 2005;Dupre et al, 2006). The recognition of DNA ends by the MRN complex may be a prerequisite for its DNA unwinding, tethering or nuclease activities implicated in ATM activation (Uziel et al, 2003;Costanzo et al, 2004;Jazayeri et al, 2008). Thus, it seems likely that the MRN complex and 53BP1 function both upstream and downstream of ATM after DNA damage.…”
Section: Pig3 Is Involved In the Cell-cycle Checkpoint Pathwaymentioning
confidence: 99%
“…Recent studies have indicated that the MRN complex bound to DNA ends may directly activate ATM and/or initiate the nucleation of ATM at DSBs, which leads to its activation (Lee and Paull, 2005;Dupre et al, 2006). The recognition of DNA ends by the MRN complex may be a prerequisite for its DNA unwinding, tethering or nuclease activities implicated in ATM activation (Uziel et al, 2003;Costanzo et al, 2004;Jazayeri et al, 2008). Thus, it seems likely that the MRN complex and 53BP1 function both upstream and downstream of ATM after DNA damage.…”
Section: Pig3 Is Involved In the Cell-cycle Checkpoint Pathwaymentioning
confidence: 99%
“…However, there is increasing evidence that by-products of DNA repair have the potential to impact cell signaling events (15)(16)(17)(18). Moreover, defects in the clearance of DNA oligonucleotides are associated with various autoimmune disorders (19 -21), and abnormal localization of DNA in the cytosol may be sensed by the innate immune system (22,23).…”
mentioning
confidence: 99%
“…7 DSB repair is believed to involve an Atm to Atr switch. 8,9 Atm is first recruited to DSBs and ssDNA is later generated by resection of the DNA ends, where Atr can be assembled and activated. Thus, there exists a complex functional interaction between these two PIKKs.…”
mentioning
confidence: 99%